Partial discharge measurement in solid dielectric of H.V Cross-linked polyethylene (XLPE) submarine cable - Rasha Abdul-nafaa Mohammed; Ali Nathem Hamoodi; Bashar M. Salih (Institute of Advanced Engineering and Science, 2020)
A partial discharge described as anon-linear electrical break-down even that happened in a section of insulating area between two conduct which are at different potentials the damage of the insulating material, these conductors have a different insulating material potential of damage, under AC voltage discharge interval process. In this paper, we propose a Matlab /Simulation software. A detailed analysis of the partial discharge (PD) signal in the underground electric power conductor performed for monitoring, and investigation of numerous effects associated with the partial discharge event, such as heat ,phonic and electrical. Thus, to gain the important data of the insulating material status.